Leading with integrity : creating positive change in organizations - Smith, Michael, 1947 July 14- (Routledge, Taylor and Francis Group, 2019)
Thanks to global news and social media, we are the most informed and socially conscious generation in history. But what are the sources of inner inspiration that guide our daily conduct and motivations in the workplace? Far from the old Machiavellian dictum that "the ends justify the means", the reverse is often the case: the means determine the ends. This book presents the stories of business leaders who have aimed to build trust in the economy, and have delivered value through integrity, cooperation, stewardship, purpose and sustainability. It proposes the eight Cs of trust which can define the culture of organizations: contracts, covenants, competences, character, conscience, conviction, courage and change. The book makes the clearlink between personal decision-making and global outcomes and demonstrates how positive decision-making can lead to change inside organizations and beyond.